Considerations for Choosing the Right Rootstocks - William S. Castle; James J. Ferguson (EDIS)
Choosing a rootstock is an important decision. It should be carefully considered because the decision is a relatively permanent one and, therefore, has long-term significance. The steps in choosing a rootstock may not always be obvious, but there are several factors that traditionally have been important.  Some of the steps and factors involved are described in this publication in a generalized approach to selecting the best rootstocks for your conditions. Use this fact sheet as as a handy check-off form when preparing to select rootstocks. This document is HS932, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: June 2003.